THEORY OF USE OF 3D GRAPHIC VISUALIZATION TECHNOLOGIES IN TEACHING TECHNICAL SPECIALTIES - Shaynazarov Ravshan Mamayusubovich (American Journals, 2024)
In the context of an informed society, the development of Information Communication will create the world of hi-tech, the important stages of the development of the education of our country, the equipment of educational institutions with digital and modern educational technologies.
Keywords: 3D technologies have been developed for the “technical and information understanding of visualization, the transformation of internal mental content into one or another visual image, the success of infographics in education, engineering graphics” courses.